Penanaman Nilai-nilai Karakter Melalui Kegiatan Literasi dalam Mata Pelajaran Sejarah Kebudayaan Islam Di MTS N 4 Hulu Sungai Utara Kalimantan Selatan - NELA SYARAH VIKRATI NELA; Muhammad Fauzil 'Adzim (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
This article discusses the cultivation of character values in students through literacy activities in the form of making posters, wall paper and literacy trees, especially at MTs N 4 Hulu Sungai Utara, South Kalimantan in the subject of Islamic Cultural History. The inculcation of these character values is carried out first, through conceptual literacy activities directing students to inculcate values so that they become independent, responsible, disciplined, hard work and creative individuals. Second, the inculcation of character values that is applied is the goal of education as a whole. Third, there are several obstacles in implementing literacy activities such as not knowing the intended literacy activities, decreasing the enthusiasm of students in carrying out activities and requiring quite a long time to carry out these activities. So it can be concluded that the inculcation of character values of students through literacy activities at MTs N 4 Hulu Sungai Utara, South Kalimantan is a form of humanization of education and as an effort to cultivate character values students, so that students have good character.